Hybridization of Images: Film/Painting - Melro Salzedas, Nelyse A.; Paccola, Rivaldo Alfredo (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2016)
This paper discusses the hybridization of images of paintings and film particles in Italian and American films, including establishing a metaphorical field whose interstitium a common field to both arises. The Italian critic De Santi (Cinema and pittura, 2008) brings up this process of hybridization: Pasolini, the film "Rage" (1963), uses the backdrop of the screen Rosso Fiorentino, "The Descent from the Cross" (1521); in another, "Mamma Roma" (1962) and Fellini, "Satyricon" (1969), inspired by the Mantegna screen "Dead Christ" (1485). Also, Newel (Mona Lisa smile, 2003) uses Picasso screen (Demoiselles D'Avignon, 1907) as a pedagogical discourse of the protagonist.